Lignin p-Hydroxybenzoylation Is Negatively Correlated With Syringyl Units in Poplar - Mottiar, Yaseen; Mansfield, Shawn D. (Frontiers in Plant Science, 2022)
The lignin found in the cell walls of poplar fibres is decorated with ester-linked p-hydroxybenzoate moieties that originate from the participation of acylated monolignols in lignin polymerisation. Although little is known about the biological implications of these cell wall constituents, it has historically been postulated that acylated monolignols might promote lignification in syringyl lignin-rich species such as poplar. However, cell-wall-bound p-hydroxybenzoate groups were negatively correlated with syringyl units in a collection of 316 unrelated genotypes of black cottonwood (Populus trichocarpa). Based upon this observation, several alternative hypotheses on the occurrence of lignin acylation are presented.